2007
DOI: 10.1038/sj.ki.5002346
|View full text |Cite
|
Sign up to set email alerts
|

When a friend can become an enemy! Recognition and management of metformin-associated lactic acidosis

Abstract: A 78-year-old woman presented with a 3-day history of abdominal pain, nausea, vomiting, and anorexia. Past medical history included type 2 diabetes mellitus, autoimmune hepatitis, hypertension, and ulcerative colitis with colectomy. Medications included metformin 1500 mg twice daily (6 months), glyburide, rofecoxib, furosemide, levothyroxine, prednisone, azathioprine, and propanolol. On admission, she was hypothermic (34.41C), had blood pressure, 115/51 mm Hg, pulse 104 beats/min, and trace of lower extremity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…While the incidence of MALA is low, its mortality is reported to approach 50 % [2,12,15,16,19,24,26]. The estimated incidence of lactic acidosis in chronic users of metformin is between three and nine cases per 100,000 patients-years [1,3,10,13,15,27]. However, a 2011 study found a MALA incidence of 47 cases per 100,000 patient-years-at least five times higher than the previously reported rates [13].…”
Section: How Does Metformin Lead To the Development Of Lactic Acidosimentioning
confidence: 55%
See 4 more Smart Citations
“…While the incidence of MALA is low, its mortality is reported to approach 50 % [2,12,15,16,19,24,26]. The estimated incidence of lactic acidosis in chronic users of metformin is between three and nine cases per 100,000 patients-years [1,3,10,13,15,27]. However, a 2011 study found a MALA incidence of 47 cases per 100,000 patient-years-at least five times higher than the previously reported rates [13].…”
Section: How Does Metformin Lead To the Development Of Lactic Acidosimentioning
confidence: 55%
“…Though the mechanism is not well described, hypoglycemia and, less commonly, hyperglycemia have also been reported in severe poisonings [29]. Metforminassociated lactic acidosis with therapeutic dosing has up to a 50 % mortality rate [10,26]. However, the lactic acidosis resulting from intentional acute ingestions is less well understood.…”
Section: How Does Metformin Lead To the Development Of Lactic Acidosimentioning
confidence: 99%
See 3 more Smart Citations